Are anti-SARS-CoV-2 S/N IgG/IgM antibodies always predictive of previous SARS-CoV-2 infection? - Lippi Giuseppe; Henry Brandon M.; Pighi Laura; De Nitto Simone; Salvagno Gian Luca (Advances in Laboratory Medicine, 2023)
We planned this study to verify whether immunoassays for quantifying anti-SARS-CoV-2 IgG/IgM antibodies against both spike (S) and nucleocapsid (N) proteins may be used for identifying previous SARS-CoV-2 infections.